Les colonies de vacances en France, 1944–1958: impulsions politiques autour d'un fait social majeur. (3rd September 2017) - Fuchs, Julien
Abstract: This article looks at the French state's approach to the "colonies de vacances" between 1944 and 1958. Created in 1876 by the Reverend Bion in Zurich, these summer camps originated as a charitable institution: their initial purpose was to provide rural retreats and to restore the health of poor urban youth. Set up on French soil in 1880, these institutions gradually grew in France in the late nineteenth and early twentieth centuries. Considered both as complements to the republican school and as extensions of the "patronages" (parish unions), they were important for children and adolescents from the industrial city suburbs, and were enshrined in the leisure policies of the Popular Front from 1936 onwards. After the Second World War, summer camps in France became a major social institution (300, 000 children went to summer camps in 1945, 900, 000 in 1949) in response to both hygiene and educational needs. Based on the archives of the Directorate of Youth Movements and Popular Education (1944–1947) and the General Directorate of Youth and Sports (1948–1958), this article aims to examine the politics behind the organisation of these summer camps and to demonstrate the social and political importance of these popular educational institutions which, in 1957, involved 1.35 million French children and teenagers. Although the history of French summer camp federations (UFCV, CEMEA, CPVC, UFOVAL, etc.) has been widely studied, how the state sees its role and influences these organisations has mostly been considered indirectly. The intention is to show that among the educational, cultural and sports policies implemented during the Fourth Republic in France, those related to the organisation of "colonies de vacances", and therefore the organisation of holidays for a very large number of children and teenagers, occupy a significant place. In 1944, the summer camps were widely supported by the French state, which also planned to regulate this booming sector. The creation of qualifications for summer camp staff and directors in 1949 obliged organisations to start training schemes: they trained staff and directors to work in the municipal camps, associations, etc. Security issues led to the state tightening control of the summer camps, their recruitment and their activities. There was a great deal of political investment in these "colonies de vacances" during this period, and this was reflected in the creation of a Ministerial Education Committee in 1950, a general and regional body of inspectors for these camps, etc. However, the considerable expansion of summer camps posed increasing problems at the national political level resulting in changes to the initial subsidy policies. The State played a major part in crucial issues such as the sociological diversification of these institutions and the changes in their social role according to evolving sociocultural trend. The fact remains that the "colonies de vacances" were for the French state a centrepiece of the "popular education" that the political actors of the Fourth Republic wanted to implement in order to build the France of the post-war period..